The Comic Elements in William Faulkner's The Reivers - Arif, Saffeen Nu'man (جامعة بغداد - كلية التربية ابن رشد, 2012)
مما لاشك فيه أنّ الروائي الاميركي وليم فوكنر (١٨٩٧-١٩٦٢)، من بين الرموز الادبية الاميركية الاخرى، يشغل موقعا متميّزاَ كأحد روّاد الرواية الاميركية الحديثة. لقد استوحى النقّاد من أعماله العديد من المحاولات لدراستها وتحليلها وتقييمها بقدر عدد التفسيرات المحتملة التي قد تتمخض عنها دراسة كل من تلك الأعمال. \ ولأن روايات فوكنر، كغيرها من الأعمال الأدبية، يمكن النظر اليها من مختلف الزوايا والمنظورات، فان هدف البحث هو تسليط بعض الضوء على احدى تفسيرات روايته الأخيرة ،اللصوص (١٩٦٢)، ككوميديا الغرض منها هو السخرية من سلوكيات وحماقات صنف أو طبقة اجتماعية معينّة في موطن فوكنر الأصلي، أي الجنوب الاميركي القصي. كما ويحٍاول ابراز معالجة فوكنر البارعة لموضوعه ومقدرته على التعامل معه بطريقة تسمح له بإيصال رسالته، التي لا بد من ارتباطها بموضوعه الأثير المتمثل بمشاكل القلب البشري. Undoubtedly, the American novelist William Faulkner (1897-1962) occupies a unique position, among other American literary figures, as one of the pioneers of modern American novel. For decades, the works of Faulkner have inspired as many attempts by critics to study, analyze, and evaluate them as the number of potential interpretations that studying each work may still yield. \ As Faulkner's novels, like any other literary work, can be viewed from different angles or perspectives, the goal of this paper is to shed some light on one of the readings of his last novel, The Reivers (1962), as a comedy whose purpose is to ridicule the manners and follies of certain classes in Faulkner's native land, namely, the American Deep South. It also attempts to show Faulkner's masterful approach of his topic and his capacity to handle it in such a way as to convey his vision, which indeed has to do with his favorite subject; that is, the human heart and its problems
ملخص لبحث منشور باللغة الانجليزية
Keywords: الانتاج الادبي -- مستخلصات الابحاث -- فوكنر ، وليم -- التراجم -- الادباء الامريكان -- الروايات الانجليزية